Designing a Model of Tourism Village by Augmenting Language and Tourism Awareness as an Attempt to Increase Local Economy in Batu - Junining, Esti; Purwaningtyas, Isti; Khasanah, Ismatul; Hartono, Didik (International Journal of Social and Local Economic Governance, 2017)
As one of the efforts to awaken the local economy of Batu, this study offers a model of language and tourism awareness-based-tourism village that is establishing a tourism community that actively supports the government tourism programs. On the basis of the need analysis of the local people, a material for learning English for tourism and a model of tourism village were set up in the first year of the study. The programs in the second year of the study focus on the development and implementation of the tourism community. This community works on increasing communication skills and tourism awareness among the community consisting of a group of tourism awareness, the youths and businessmen. A visit and training plan in the form of Focus Group Discussion (FGD) has already been implemented in the four villages in Batu namely Punten, Tulungrejo, Sumberejo and Pandanrejo. This community is established to increase the local people income which is expected to influence the global income of the village. The results show that the four villages agree with the idea of training and building a tourism community in Batu.Keywords: developing a model of tourism village, communication skill awareness, tourism awareness, local economy, Batu city